Flexible asymmetric supercapacitor with high energy density based on optimized MnO2cathode and Fe2O3anode - Liu, W.; Zhu, M.; Liu, J.; Li, X.; Liu, Jian (2018)
© 2018 All-solid-state flexible supercapacitors have shown great potential in wearable and portable electronics. In this work, a flexible asymmetric pseudocapacitor (FAPC) is fabricated by using MnO2nanosheets-carbon fabric as cathode and Fe2O3nanowire-carbon fabric as anode in the presence of PVA-LiCl as gel electrolyte. With high area capacitances of MnO2and Fe2O3based electrodes by optimizing the reaction conditions, the device shows high working potential of 1.8 V, high area capacitance of 83.3 mF/cm2(119 F/g), stable cycling performance with 82.3% of capacitance retention after 5000 cycles, and a competitive energy density of 53.55 Wh/kg in the broader context of MnO2-based supercapacitors. In addition, the FAPC demonstrates excellent mechanical stability and flexibility with negligible degradation of electrochemical performance after numerous bending tests, establishing it as a promising candidate for portable and wearable energy storage.